Efficient k-coverage scheduling algorithms for wireless sensor networks / Ahmed Abdullah Saleh Al-Shalabi - Saleh Al-Shalabi, Ahmed Abdullah (Institute of Graduate Studies, UiTM, 2014)
Sensors are tiny devices, which consume low power and are inexpensive; they are used in many applications, such as, military surveillance, target tracking, forest-fire alarm. Many applications require k-coverage network to ensure the quality of the monitored area, where every single point is assured to be concurrently covered by a minimum of k sensors. Meanwhile, the network that provides more than the required k-coverage degree does not enhance the performance, but just increases the number of working sensors, and shortens the network lifetime. Preserving the requested k-coverage for Wireless Sensor Networks, while prolonging the network lifetime with a small computation cost, is a major challenge. This research demonstrates distributed and energyefficient k-coverage scheduling algorithms that preserve the required k-coverage and prolong the network lifetime. An efficient k-coverage algorithm for sensors with fixed sensing range (Maximum Layers Scheduling algorithm - MLS) is demonstrated. MLS efficiently builds maximum number of layers, where, each layer consists of a disjoint set of working sensor nodes that conserve 1-coverage for the whole monitored area, and 1-connection that guarantees each layer is connected, and can individually deliver the data reporting to the base station.